2020
DOI: 10.1504/ijpm.2020.110083
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with the stipulated procurement process in local governments: a case from a developing nation

Abstract: Empirical evidence of compliance or otherwise with procurement laws especially in developing nations is limited despite its importance in ensuring quality project delivery. This research assessed compliance with the procurement law in the local government setting of a developing nation, challenges to compliance and workable solutions. A total of 108 copies of a carefully structured questionnaire was administered to individuals concerned with contract administration in the local governments in the study area an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 20 publications
(31 reference statements)
3
17
0
Order By: Relevance
“…Besides, the micro-enterprises are still at the survival stage; therefore, due diligence to stipulated EMS guiding documents may not be carefully considered in the organisations. These findings corroborate the submission of Adeniyi et al (2020) that most of the lower-tier organisations do not comply with stipulated processes written in manuals or other guiding documents. The difference in the opinions of the quantity surveyors and the engineers on the 'Environmental performance tracking (D7)' could be linked to the professional training of the quantity surveyors in ensuring an approximate or precise quantity/calculation on any elements on construction projects.…”
Section: "Table 5" Heresupporting
confidence: 82%
See 1 more Smart Citation
“…Besides, the micro-enterprises are still at the survival stage; therefore, due diligence to stipulated EMS guiding documents may not be carefully considered in the organisations. These findings corroborate the submission of Adeniyi et al (2020) that most of the lower-tier organisations do not comply with stipulated processes written in manuals or other guiding documents. The difference in the opinions of the quantity surveyors and the engineers on the 'Environmental performance tracking (D7)' could be linked to the professional training of the quantity surveyors in ensuring an approximate or precise quantity/calculation on any elements on construction projects.…”
Section: "Table 5" Heresupporting
confidence: 82%
“…Interestingly, Li et al (2019a) revealed that the government's effort and the educational knowledge of construction professionals are fundamental to environmental practices in the Chinese construction industry. This is because, the availability of a vital policy document does not guarantee compliance with the dictates of the policy (Adeniyi et al, 2020). However, creating public awareness and a sense of social responsibility on the subject matter must precede any policy enforcement (Ikram et al, 2019;Babiak and Trendafilova, 2011).…”
Section: Drivers Of Environmental Management Systemmentioning
confidence: 99%
“…Thus, compliance with the code of ethics of the QS profession is one of the panaceas for its relevance and sustainability in the built environment of developing countries. Therefore, compliance with code of conduct is important, as it is possible to have standards written in guiding documents of a professional institution and not being practised by the concerned professionals (Adeniyi et al, 2020).…”
Section: Components Interpretationmentioning
confidence: 99%
“…The federal and the state governments possess most of the powers and authorities in the country, and with this, regulations of industrial actions are being carried out. The local government often acts on the directives of the state government (Adewale, 2009;Adeniyi et al, 2020); thus, it could be inferred that state government is su cient for discussion in this study since the local government act on the interest and delegations from the state government. This analysis shows that the regulation of the federal government coupled with enforcement actions on the part of the state government plays a fundamental role in GSCM in the manufacturing industry.…”
Section: Government-related Drivermentioning
confidence: 94%
“…For instance, countries of the world like America and Denmark have on many occasions adopted market-based methods, voluntarism as well as other plain policy resourcefulness like incorporation; conglomerates; membership; purposeful elegances of decision-making; erudition; collaboration, and New Environmental Governance (NEG) to control environmental dreadful conditions Holley, 2017). Therefore, enforcement of the regulations is important to achieve the aim of formulating the policy (Koski, 2006;Adeniyi et al, 2020).…”
Section: Drivers Of Green Supply Chain Managementmentioning
confidence: 99%